2021
DOI: 10.2147/idr.s342652
|View full text |Cite
|
Sign up to set email alerts
|

CRP/Albumin Has a Promising Prospect as a New Biomarker for the Diagnosis of Periprosthetic Joint Infection

Abstract: Purpose:In the present study, we aimed to identify more effective biomarkers for the diagnosis of periprosthetic joint infection (PJI) by comparing the diagnostic ability of C-reactive protein (CRP)/albumin, systemic immune-inflammation index (SII), and existing biomarkers. Methods: In this single-center retrospective analysis, 216 patients who underwent revision knee or hip arthroplasty from June 2013 to June 2021 and met the inclusion and exclusion criteria were analyzed, including 80 patients in the PJI gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Another study by Shi et al demonstrated that CRP/albumin gave excellent performance in the diagnosis of PJI, with an AUC of 0.941, which was better than those of CRP (0.937) and ESR (0.914) [25]. Inspired by the research of Shi et al, we used CRP/AGR as a novel biomarker to predict PJI, and found that this reduced the error associated with the use of either CRP or AGR to diagnose infection [25]. For the first time, we found that CRP/AGR gave better performance than CRP and ESR, with an AUC of 0.902.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study by Shi et al demonstrated that CRP/albumin gave excellent performance in the diagnosis of PJI, with an AUC of 0.941, which was better than those of CRP (0.937) and ESR (0.914) [25]. Inspired by the research of Shi et al, we used CRP/AGR as a novel biomarker to predict PJI, and found that this reduced the error associated with the use of either CRP or AGR to diagnose infection [25]. For the first time, we found that CRP/AGR gave better performance than CRP and ESR, with an AUC of 0.902.…”
Section: Discussionmentioning
confidence: 97%
“…A retrospective study by Shang et al reported that the level of GLB was significantly elevated and the level of AGR was significantly decreased in a PJI group, with an AUC of 0.784 for GLB and 0.826 for AGR [18]. Another study by Shi et al demonstrated that CRP/albumin gave excellent performance in the diagnosis of PJI, with an AUC of 0.941, which was better than those of CRP (0.937) and ESR (0.914) [25]. Inspired by the research of Shi et al, we used CRP/AGR as a novel biomarker to predict PJI, and found that this reduced the error associated with the use of either CRP or AGR to diagnose infection [25].…”
Section: Discussionmentioning
confidence: 98%
“…Based on our results, the AUC for CRP/albumin (0.91) was only slightly lower compared with ESR, and it also showed good sensitivity (82.1%) and specificity (92.5%) for diagnosing PJI, which was similar to our previous findings. 13 As one of the traditional inflammatory biomarkers, ESR is often used as a reference for evaluating other new biomarkers. In 2011, MSIS first identified elevated serum CRP and serum ESR as secondary criteria for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, MSIS first identified elevated serum CRP and serum ESR as secondary criteria for diagnosis. 13 In the newest modification of the ICM criteria, even though the diagnostic value of D-dimer for PJI still remains controversial, it is given two points, while ESR is given lower points. 12 In the present study, ESR received attention for its excellent diagnostic value in PJI of males.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] An emerging predictive marker, the C-reactive protein (CRP)-to-albumin ratio (CAR), has been identified in other orthopaedic and nonorthopaedic surgical conditions but has not been assessed in the setting of SEA. [13][14][15] The CAR is attractive because it is a measure that can contextualize both severity of the disease state and the patient's overall general health state and potential physiologic reserve. Furthermore, all the aforementioned biomarkers are timely, cost-conscious, and routine tests with the potential to provide valuable insights into the acuity and trajectory of disease states.…”
mentioning
confidence: 99%